Applying knowledge management techniques for building corporate memories - Watson, Ian, 1960- (Amsterdam ; Boston : Morgan Kaufmann, 2003)
The wholesale capture and distribution of knowledge over the last thirty years has created an unprecedented need for organizations to manage their knowledge assets. Knowledge Management (KM) addresses this need by helping an organization to leverage its information resources and knowledge assets by "remembering" and applying its experience. KM involves the acquisition, storage, retrieval, application, generation, and review of the knowledge assets of an organization in a controlled way. Today, organizations are applying KM throughout their systems, from information management to marketing to human resources. Applying Knowledge Management: Techniques for Building Corporate Memories examines why case-based reasoning (CBR) is so well suited for KM. CBR can be used to adapt solutions originally designed to solve problems in the past, to address new problems faced by the organization. This book clearly demonstrates how CBR can be successfully applied to KM problems by presenting several in-depth case-studies. Ian Watson, a well-known researcher in case-based reasoning and author of the introductory book, Applying CBR: Techniques for Enterprise Systems has written this book specifically for IT managers and knowledge management system developers. * Provides 7 real-world applications of knowledge management systems that use case-based reasoning techniques. * Presents the technical information needed to implement a knowledge management system. * Offers insights into the development of commercial KM CBR applications * Includes information on CBR software vendors, CBR consultants and value added resellers.
Preface; Knowledge Management and Organizational Memory; Understanding Case-Based Reasoning; Managing Product Quality: Total Recall at National Semiconductor; Developing Expertise: Color Matching at General Electric Plastics; Improving Process Design: Knowledge Sharing in an Aluminum Foundry; Benchmarking Best Practice: Internal Financial Control at Deloitte Touche; Information Retrieval: Intelligent Online Product Selection for Analog Devices; Distributed Sales Support: Web-Based Engineering at Western Air; Personalizing Information Services: Intelligent Digital TV at ChangingWorlds; Lessons Learned; Appendix Resources; Index.
Includes bibliographical references and index.
Keywords: Knowledge management -- Case studies; Corporations -- History; Electronic books; Case studies